Can Mixed-Reality Improve the Training of Medical Procedures? - Azimi, Ehsan; Winkler, Alexander; Tucker, Emerson; Qian, Long; Doswell, Jayfus; Navab, Nassir; Kazanzides, Peter (Proceedings of the Annual International Conference of the IEEE Engineering in Medicine and Biology Society, EMBS, 2018)
One cause of preventable death is a lack of proper skills for providing critical care. The conventional course taught to non-medical individuals involves instructions of advanced emergency procedures routinely limited to a verbal block of instructions in a standardized presentation (for example, an instructional video).In the present study, we evaluate the benefits of using an OST-HMD for training of caregivers in an emergency medical environment. A rich user interface was implemented that provides 3D visual aids including images, text and tracked 3D overlays corresponding to each task that needs to be performed. A user study with 20 participants is conducted which involves training of two tasks where each subject performs one task with the HMD and the other with standard training. Two evaluations were performed, with the first immediately after the training followed by a second one three weeks later. Our results indicate that using a mixed reality HMD is more engaging, improves the time-on-task, and increases the confidence level of users in providing emergency and critical care.
CRIS-Team Scopus Importer:2023-03-08